MENINGKATKAN MINAT BACA ANAK PADA TAMAN BACAAN MASYARAKAT “KELAS TERAS” - Siti Nurul Iftitah (MAJU : Indonesian Journal of Community Empowerment, 2026)
Reading is the foundation of all learning. However, in this digital era, fostering an interest in reading among children has become an increasingly significant challenge; exposure to gadgets and instant entertainment often overshadows the appeal of books. Cultivating a reading habit from an early age is crucial for shaping children into lifelong learners with broad horizons and the ability to think critically and creatively. This activity took place on October 12, 2025, at the *Kelas Teras* Community Reading Center (*Taman Bacaan Masyarakat*), located at Ndalem Rongkot Pendowo, Kranggan, Temanggung. The children participated enthusiastically from start to finish, thanks to an educational approach that was informal, relaxed, and enjoyable. As a result of this activity, the children became more motivated to read books in their daily lives—particularly at the *Kelas Teras* center, which remains open for them to learn and play together.